Juridical Analysis of Proof in Intellectual Property Rights Disputes that Contain Trade Secrets - Dedi Kurnia Suranta Ginting; Saidin; Tengku Keizerina Devi; Jelly Leviza (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
The aim to be achieved from this research is to analyze and find out the legal protection for trade secret holders; to analyze and find out the contractual relationship between employees and companies in maintaining and protecting Trade Secrets; and to analyze and find out the application of information confidentiality proving law in cases of violations of boiler machine trade secrets based on Supreme Court Decision No. 3305/K/Pdt/2016 dated 24 January 2017 and the Lunpia Express trade secret violation case based on Supreme Court Decision No. 2535K/Pdt/2016 dated 8 December 2016. This research used a documentation study approach with qualitative data analysis. The results of the study show that the Supreme Court's Decision No. 3305/K/Pdt/2016 dated 24 January 2017 stated that PT. HCMI was proven to have violated trade secrets by using the same production and sales methods as PT. BPE obtained from Calvin Jonathan Barus, et al as former employees of PT. BPE. This is inseparable from the verification process which proves that PT. BPE is the first distributor of boiler machines that have economic value and keep their production methods secret.